The Activity of Plasma, Serum, Thrombin, and Plasmin toward Synthetic Trypsin Substrates - Szczeklik, E; Orłowski, M; Szczeklik, A; Narczewska, Barbara (Thrombosis and Haemostasis, 1968)
P-toluenesulphonyl-1-arginine methyl ester and two amide substrates of arginine (Nα-benzoyl-dl-arginine-p-nitroanilide and Nα-benzoyl-dl-arginine-2-naphthylamide) were employed for studies of the nature of the “trypsin-like” activity in plasma, serum and euglobulins. No data were obtained which might suggest the presence of trypsin activity in either plasma or serum. The evidence indicates that activity toward both amide substrates in plasma and euglobulins is dependent on the generation of thrombin. Activation of plasminogen in euglobulins by streptokinase generated a proteolytic activity toward Nα-benzoyl-dl-arginine-p-nitroanilide but not toward Nα-benzoyl-dl-arginine-2-naphthylamide. The generation and inactivation of thrombin activity in whole plasma may be conveniently followed by using Nα-benzoyl-dl-arginine-p-nitroanilide as substrate.Purified preparations of thrombin and plasmin were shown to split several synthetic amide substrates of arginine. Significant differences between thrombin and plasmin were found in the rate of reaction with these substrates. Of the amide substrates, Nα-carbobenzoxydiglycyl-l-arginine-2-naphthylamide was split most rapidly by both enzymes. This substrate may be conveniently used for the determination of thrombin and plasmin activity.